PREVALENCE OF ENDEMIC GOITER IN HILLY AREAS OF MARDAN AND SWABI DISTRICTS - Khan, Noor Ahmad; Jadoon, Huna; Khan, Jahangir A.; Umbatcth, Martin (Journal of Ayub Medical College Abbottabad, 2000)
Background: A goiter prevalence survey was conducted during October 1988 lo September, 1989 in the project area of Pak-German Integrated Rural Development Program (IRDP). Methods: 22 villages from 7 union councils were randomly selected. 8803 persons were clinically examined for the presence of goiter and sociodemographic parameters were studied. Results: A total of 1048 (11.9%) people out of 8803 people were found to have goiter. Large size of goiter was least common while palpable goiter had high prevalence. Women of child bearing age had the highest prevalence followed by girls and boys from 1-15-year age. The prevalence among adult males was the lowest. It was observed that percent prevalence with age in females increased while in males the percent prevalence showed increase up to the age of 15, while it was lower at higher ages.